1998
DOI: 10.1161/01.cir.97.20.2049
|View full text |Cite
|
Sign up to set email alerts
|

Gene for Arrhythmogenic Right Ventricular Cardiomyopathy With Diffuse Nonepidermolytic Palmoplantar Keratoderma and Woolly Hair (Naxos Disease) Maps to 17q21

Abstract: Background —Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a heart muscle disease of unknown etiology that causes arrhythmias, heart failure, and sudden death. Diagnosis can be difficult, and this hampers investigation of its molecular basis. Forms of ARVC in which gene penetrance and disease expression are greater should facilitate genetic study. We undertook a clinical and genetic investigation of Naxos disease, originally described by Protonotarios in 1986. This disease constitutes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
114
0
5

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(119 citation statements)
references
References 66 publications
0
114
0
5
Order By: Relevance
“…Initial mapping of this disorder pointed to the chromosomal locus 17q21, 8 and candidate-gene sequencing within this region revealed a homozygous 2 bp deletion (c.2157-2158delGT) in the junction plakoglobin gene (JUP) that was present only in affected individuals (Figure 2A). 9 Subsequent studies showed that among subjects homozygous for this mutation, the disease is completely penetrant by adolescence.…”
Section: Mutations Plakoglobinmentioning
confidence: 99%
“…Initial mapping of this disorder pointed to the chromosomal locus 17q21, 8 and candidate-gene sequencing within this region revealed a homozygous 2 bp deletion (c.2157-2158delGT) in the junction plakoglobin gene (JUP) that was present only in affected individuals (Figure 2A). 9 Subsequent studies showed that among subjects homozygous for this mutation, the disease is completely penetrant by adolescence.…”
Section: Mutations Plakoglobinmentioning
confidence: 99%
“…Several genetic loci have been reported to be associated with the disease and mutations in six genes have been identified: ryanodine receptor, plakoglobin, desmoplakin and recently transforming growth factor-β, plakophilin-2 and desmoglein. [9][10][11][12][13][14][15][16] Patients with mutations in the ryanodine receptor gene, also called ARVC2, are more prone to develop arrhythmias. 17 The recognition that ARVC is frequently familial and can cause arrhythmic death leads to the challenge to identify family members who are at risk.…”
Section: Discussionmentioning
confidence: 99%
“…A familial predisposition for ARVD has been described, suggesting that a genetic factor may be involved. [1][2][3][4][5][6][8][9][10][11][12][13][14][15][16] Only 10% of patients are diagnosed before the age of 20, probably because the arrhythmia is not apparent during this stage of life. However, patients with ARVD have an increased risk of cardiac sudden death.…”
Section: Discussionmentioning
confidence: 99%
“…25) A screening test for detecting patients with ARVD is needed, since the SAECG procedure is neither complicated nor time consuming (about 10 minutes). 15) Moreover, it is cost-effective and only reguires 1 meter of recording paper. The reasons why we utilizede time domain method instead of frequency domain method to study the SAECG are as follows: 26,27) 1) Time domain method is well established and has good reproducibility, 2) Frequency domain method is well utilized.…”
Section: Discussionmentioning
confidence: 99%